"[E]ven Though We Don't Have Everything…We Build Our Own Thing": Exploring Black Girl Space. (25th November 2021) - Rogers, Leoandra Onnie; Butler‐Barnes, Sheretta T.
Abstract : In a racially stratified and oppressive society, Black youth must figure out who they are and what they can achieve while navigating dehumanizing stereotypes that devalue and disregard Black lives. In the current paper, we analyze focus group interviews with Black students at a predominately Black, all‐girls high school to understand the meaning, significance, and potential of Black girl space through an intersectional and developmental lens. Results revealed the challenges and opportunities particularly with regard to the relational space (peers, sexuality, identity) and the structural space (extracurriculars, policies, and building structure). We discuss the potential of Black girl space and the broader implications for educational spaces to support Black girls' development to create a more equitable and impactful developmental science.